When Affordable Housing Comes Up Against Environmentalism: Legal Lessons from Minnesota and California - Siegman, Reuben (Journal of affordable housing & community development law, 2023)
.190 Two of the most important issues that the country is facing often find themselves at odds with each other: the way that the country balances environmental protections and affordable housing.1 Environmentalism and the climate are increasingly important to voters as we face a changing world due to the risk from global warming.2 Moreover, the Biden administration has prioritized these issues, including passing the largest climate law in the history of the country in the Inflation Reduction Act.3 Affordable housing is another important policy area, with a plurality of Americans saying it is a major issue, with those who are younger, and those who live in urban areas in particular, believing it is a significant issue.4 While national policy impacts housing affordability, many important decisions are left to municipalities, and substantial advocacy takes place at the city level.5 Policies that favor affordability often involve producing more affordable housing-which involves building.6 And any environmentalist will probably tell you that when you build, you must think about the impacts on the environment and comply with environmental regulations. "7 These laws are generally similar to the federal version of the law, but may vary slightly on a state-by-state basis.8 Though some are action forcing (e.g., California and New York), most are procedural and state that when state or local governments take a major action that could significantly impact the environment, they must complete an environmental review.9 Importantly, this requirement usually includes local or municipal agencies that conduct zoning, land use and site-approval decisions, and permitting, all of which may be subject to environmental reviews.10 These environmental regulations may increase costs for developers, create uncertainty around projects, and can result in delays for projects.11 Recently, NIMBYs12 have used these environmental protections (often in bad faith) to stop or delay housing projects through litigation or the threat of litigation.13 One study in California found that challenging housing projects, and especially higher density housing, is the most frequently challenged type of private sector project under the California Environmental Quality Act (CEQA).14 To build more housing to increase affordability (and density, helping climate goals), projects go through these "Little NEPAs," which NIMBY groups have often used to delay or block projects.15 Importantly, the states that have the strongest environmental protections are often the states that also face the biggest shortages of affordable housing and are home to popular metropolitan areas.16 States like California, Massachusetts, and New York are considering reforming these environmental laws to make it easier to build more housing.17 This possibility has created a significant tension between urbanism and environmentalism: the need to build more affordable housing quickly, while balancing the level of environmental protections that states and municipalities should have, which often slow, delay, or increase the cost of building. [...]I will conclude by comparing how the efforts at reform for each have played out and the importance of the role of the state government in approaches to solve the tension between urbanism and environmentalism in the push to expand affordable housing. In Minnesota, all cities have a comprehensive plan that must be updated every decade.26 These are policy documents that often go unnoticed by the public, with cities primarily receiving input from neighborhood associations.27 In Minneapolis, a movement of progressives gained power in the city council, resulting in the city asking for feedback at more diverse forums and hearing from different constituencies.28 From this input, the city created a draft version of its next planning document, the 2040 plan, that included many policies focusing on creating more affordable housing.29 The most notable policy to come from this draft (and ultimately stay in the final document) was eliminating single-family-home zoning to allow duplexes and triplexes anywhere in the city.30 Attracting a notably diverse coalition of supporters, the plan passed the council, and Minneapolis soon became known as the first city to abolish single-family-home zoning.31 Upon its passage, the 2040 plan, and particularly the policy to end single-family-home zoning drew widespread praise, ranging from Ben Carson (Trump's HUD Secretary at the time) to many progressive leaders.32 Advocates believed that this change would allow construction of greater density, increasing supply in the market to better meet demand and lower prices in part by providing smaller units, which are more affordable than single-family homes.33 Soon other political bodies were looking at Minneapolis as an example of how to address affordable housing.34 While the details of the plan go beyond simply ending single-family-home zoning, this is certainly what grabbed attention, as well as the diverse and somewhat unlikely coalition that came together to support the plan: labor groups, racial justice supporters, business interests, climate advocates, as well as some libertarians.35 B. Legal Implications Even though it gained a wide net of supporters, the plan was still controversial and plenty of groups advocated against its passage and fought to ensure that it did not get implemented.36 Their opposition culminated in a lawsuit to stop the vote from happening three days before the scheduled vote by Smart Growth Minneapolis, a NIMBY organization formed in the wake of the 2040 plan, along with the Audubon Chapter of Minneapolis and Minnesota Citizens for the Protection of Migratory Birds.37 While the lawsuit did not stop the scheduled vote, it continued after the vote, claiming that Minneapolis had violated the Minnesota Environmental Rights Act (MERA).38 After Smart Growth lost at the district and appellate levels in state court, the Minnesota Supreme Court took up the issue in early 2021.39 That court faced two primary questions: (1) "whether the rule exempting comprehensive plans from environmental review under МЕРА [Minnesota Environmental Protection Act] also exempts comprehensive plans from actions brought under MERA"; and (2) "whether Smart Growth's complaint 'sets forth a legally sufficient' claim for relief.